Measuring Motivation and Reward‐Related Decision Making in the Rodent Operant Touchscreen System. Issue 1 (4th January 2016) - Heath, Christopher J.; Phillips, Benjamin U.; Bussey, Timothy J.; Saksida, Lisa M.
Abstract: This unit is designed to facilitate implementation of the fixed and progressive ratio paradigms and the effort‐related choice task in the rodent touchscreen apparatus to permit direct measurement of motivation and reward‐related decision making in this equipment. These protocols have been optimized for use in the mouse and reliably yield stable performance levels that can be enhanced or suppressed by systemic pharmacological manipulation. Instructions are also provided for the adjustment of task parameters to permit use in mouse models of neurodegenerative disease. These tasks expand the utility of the rodent touchscreen apparatus beyond the currently available battery of cognitive assessment paradigms. © 2016 by John Wiley & Sons, Inc.